2010
DOI: 10.1111/j.1749-7345.2010.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein Requirement of Juvenile Black Sea Bream, Sparus macrocephalus

Abstract: An 8‐wk experiment was conducted to determine the optimal protein requirement of juvenile black sea bream, Sparus macrocephalus, (initial weight 13.13 ± 0.21 g, mean ± SD) in 18 300‐L indoor flow‐through circular fiberglass tanks provided with sand‐filtered aerated seawater. Six isoenergetic diets were formulated to contain varying protein levels ranging from 31.95 to 48.53% at about 3% protein increments by substituting corn oil and α‐starch for fish meal. Each diet was assigned to triplicate groups of 20 fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
48
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 80 publications
15
48
2
Order By: Relevance
“…The result shows that possibly the dietary protein was efficiently utilized by fish for protein synthesis which is in agreement with Berger and Halver (1987). Similar results have been reported in other fish species (Bai et al 1999;Kim et al 2004;Kim et al 2005;Hossain et al 2010;Zhang et al 2010). However, Kikuchi et al (1992) and Lee et al (2000) reported that PER values of olive flounder increased with increasing dietary protein levels.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The result shows that possibly the dietary protein was efficiently utilized by fish for protein synthesis which is in agreement with Berger and Halver (1987). Similar results have been reported in other fish species (Bai et al 1999;Kim et al 2004;Kim et al 2005;Hossain et al 2010;Zhang et al 2010). However, Kikuchi et al (1992) and Lee et al (2000) reported that PER values of olive flounder increased with increasing dietary protein levels.…”
Section: Discussionsupporting
confidence: 88%
“…It has high market value and consumer demand. The dietary protein requirements of several important aquaculture fish species have been determined including channel catfish, Ictalurus punctatus (Garling and Wilson 1976); Asian sea bass, Lates calcarifer (Catacutan and Coloso 1995); Indian major carp, Labeo rohita (Das et al 1991); Nile tilapia, Oreochromis niloticus (El-Sayed and Teshima 1992); olive flounder, Paralichthys olivaceus (Kim et al 2005); Korean rockfish, Sebastes schlegelii (Kim et al 2004), and Japanese eel, Anguilla japonica (Okorie et al 2007); black sea bass, Centropristis striata (Alam et al 2008); black sea bream, Sparus macrocephalus (Zhang et al 2010); and silver pomfret, Pampus argenteus (Hossain et al 2010). For most of the cultured species, dietary protein requirement has been found to be between 30 and 55 % of the diet depending on the species, fish size, dietary protein sources, and environmental condition (Hepher 1988;NRC 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Kim, Lim, Kang, K. Kim, & Son, 2012;Mohseni, Pourkazemi, Hosseni, Hassani, & Bai, 2013;Coutinho et al, 2014). In some cases, fish body protein content tends to increase with increasing protein level in the diet (Zhang, Gong, Y. Yuan, Chu, & H. Yuan, 2009;Zhang et al, 2010). However, in the current study, the protein content in the pirarucu youth fillet was not significantly affected by the dietary DP levels.…”
Section: Resultscontrasting
confidence: 46%
“…The optimal concentration of dietary protein is different among fishes and depends on the food habit (omnivorous or carnivorous). For example, the best weight gains are in pintado Pseudoplatystoma corruscans (Lundstedt et al, 2004), Mugil platanus (Carvalho et al, 2010), Sparus macrocephalus (Zhang et al, 2010). Concerning carbohydrates, the recommended amount to reach the best performance is also distinct among fishes.…”
Section: Discussionmentioning
confidence: 99%